Cranial nerve involvement in patients with MOG antibody–associated disease. Issue 2 (March 2019) - Cobo-Calvo, Alvaro; Ayrignac, Xavier; Kerschen, Philippe; Horellou, Philippe; Cotton, Francois; Labauge, Pierre; Vukusic, Sandra; Deiva, Kumaran; Serguera, Ché; Marignier, Romain
Abstract : Objective: To describe clinical and radiologic features of cranial nerve (CN) involvement in patients with myelin oligodendrocyte glycoprotein antibodies (MOG-IgG) and to assess the potential underlying mechanism of CN involvement using a nonhuman primate (NHP) model. Methods: Epidemiologic, clinical, and radiologic features from a national cohort of 273 MOG-IgG–positive patients were retrospectively reviewed for CN involvement between January 2014 and January 2018. MOG-IgG binding was evaluated in CNS, CN, and peripheral nerve tissues from NHP. Results: We identified 3 MOG-IgG–positive patients with radiologic and/or clinical CN involvement. Two patients displayed either trigeminal or vestibulocochlear nerve lesions at the root level, and the remaining patient had an oculomotor nerve involvement at the root exit and at the cisternal level. Additional CNS involvement was found in all 3 patients. None of the 3 patients' sera recognized MOG expression in CN of NHP. Conclusion: Craneal nerve involvement can coexist in patients with MOG antibody disease, although the underlying pathophysiology remains elusive.